A reverse osmosis membrane based on mixed dimensional assembly and its preparation method and application

By adopting mixed-dimensional assembly technology in the reverse osmosis membrane, combining graphene oxide nanosheets and metal oxide nanoribbons to form a highly selective reverse osmosis membrane, the problem of selectivity and permeability trade-offs in traditional membranes in high-salt wastewater treatment and seawater desalination is solved, and efficient and stable water treatment effect is achieved.

CN118718739BActive Publication Date: 2025-04-18LANZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410763400.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-04-18
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The existing polymer reverse osmosis membranes have problems of permeability and selectivity in high-salt wastewater treatment and seawater desalination, especially the structure of graphene oxide membranes is unstable when exposed to water, resulting in a decrease in selectivity.

Method used

Using hybrid dimension assembly technology, graphene oxide nanosheets are combined with metal oxide nanoribbons through coordination self-assembly to form a highly selective reverse osmosis membrane. This technology uses the strong coordination effect of metal oxide nanoribbons to form a stable structure with graphene oxide, avoiding the problem of graphene oxide film expanding in water.

Benefits of technology

The efficiency and selectivity of high-salt wastewater desalination and seawater desalination are achieved, the water flux and ion retention of the membrane are improved, and the mechanical properties are improved, solving the problem of instability of traditional membrane structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118718739B_ABST
    Figure CN118718739B_ABST
Patent Text Reader

Abstract

The present invention provides a reverse osmosis membrane based on mixed dimensional assembly and a preparation method and application thereof. The reverse osmosis membrane based on mixed dimensional assembly is obtained by coordination self-assembly of graphene oxide nanosheet material and metal oxide nanobelt material, preferably, the mass ratio of the metal oxide nanobelt material to the graphene oxide nanomaterial is 1:(0.2-6), preferably 1:(2.5-5). The reverse osmosis membrane of the present invention has excellent water flux, high ion interception rate and high mechanical stability, solves the problem that the structure and physicochemical stability of pure graphene oxide film are low and easy to swell in water, and solves the challenge that graphene oxide film is difficult to be self-supported for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of reverse osmosis membrane separation, and in particular to a reverse osmosis membrane based on mixed dimensional assembly, and a preparation method and application thereof. Background Art

[0002] In the rare earth hydrometallurgical separation process, the extraction and separation of acidic extractants is the mainstream process of the rare earth industry. In the extraction and separation process, a large amount of chemical agents are used in the acid dissolution, saponification, extraction and precipitation processes. Especially in the rare earth extraction and separation section, in order to improve the extraction efficiency, it is usually necessary to add ammonia water / NaOH to saponify the acidic extractant, resulting in a large amount of high-salt (mainly ammonium chloride / sodium chloride salt) wastewater in the rare earth smelting process. The direct discharge of high-salt wastewater in the rare earth industry will not only waste a lot of water resources, but also cause serious water environment problems. Therefore, the desalination of rare earth high-salt wastewater has always been a topic of concern and challenge.

[0003] At present, precise membrane separation technologies, such as reverse osmosis technology, have great potential in high-salinity wastewater treatment and seawater desalination. Conventional polymer reverse osmosis membranes usually have a trade-off between permeability and selectivity, which limits their large-scale application. For example, graphene oxide nanoribbons (GO NR) have abundant oxygen-containing functional groups, which makes them widely used in self-assembled membrane technology. However, since pure graphene oxide GO films are only maintained by hydrogen bonding interactions between oxygen-containing groups of graphene oxide GO nanosheets, the structural and physicochemical stability of pure graphene oxide films is low. When the membrane is immersed in an aqueous solution, hydration destroys the hydrogen bonds and expands the spacing between graphene oxide nanosheets, resulting in significant expansion of the nanochannels in the membrane. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a reverse osmosis membrane based on mixed dimensional assembly and a preparation method and application thereof.

[0005] Two-dimensional materials have inherent advantages in the preparation of membrane materials and are easy to assemble. Among them, graphene oxide has abundant oxygen-containing functional groups, can coordinate and self-assemble with metals or metal oxides, and has good film-forming properties. However, graphene oxide easily swells when it comes into contact with water or under humidity conditions, thereby losing its selectivity and making it difficult to achieve the purpose of desalination of high-salinity wastewater and seawater; water molecules will greatly weaken the interaction between graphene oxide layers, so it will swell when it comes into contact with water to produce non-selective channels. Therefore, solving the problem of graphene oxide membrane swelling when it comes into contact with water and then achieving the desalination of high-salinity wastewater and seawater is a difficulty in the current membrane material field.

[0006] In recent years, mixed matrix reverse osmosis membranes with mixed dimensional assembly have attracted wide attention in the field of high-salinity wastewater desalination and seawater desalination. This type of membrane material can use the interlayer size of the membrane to select the permeability so that water molecules with a smaller radius can quickly pass through the membrane while the solute salt molecules are retained by the membrane, thereby achieving the purpose of high-salinity wastewater desalination and seawater desalination. Therefore, self-supporting mixed dimensional assembly mixed matrix reverse osmosis membranes have become one of the main technologies for high-salinity wastewater desalination and seawater desalination today.

[0007] In a first aspect, the present invention provides a reverse osmosis membrane based on mixed dimensional assembly, which is obtained by coordination self-assembly of graphene oxide nanosheet materials and metal oxide nanobelt materials.

[0008] Water molecules will greatly weaken the interaction between graphene oxide layers, so it will swell and produce non-selective channels when it comes into contact with water. The present invention uses rigid metal oxide materials that can strongly coordinate with graphene oxide to prepare highly selective self-supporting membrane materials, which are expected to be widely used in the fields of high-salinity wastewater desalination and seawater desalination. On the one hand, the oxygen-containing functional groups of graphene oxide can form strong coordination bonds with the metals of metal oxides. On the other hand, rigid metal oxide nanobelts can be assembled with graphene oxide nanosheets in a bionic mixed-dimensional manner, which fundamentally solves the problem of graphene oxide expansion and provides advanced ideas for the preparation of high-salinity wastewater desalination and seawater desalination membranes.

[0009] In some embodiments, the mass ratio of the metal oxide nanobelt material to the graphene oxide nanomaterial is 1:(0.2-6), for example, 1:0.8, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6 or any value therebetween.

[0010] In some embodiments, the mass ratio of the metal oxide nanobelt material to the graphene oxide nanomaterial is 1:(2.5-5).

[0011] In some embodiments, the water flux of the reverse osmosis membrane is 20-300 L m -2 h -1 bar -1 , for example 30L m - 2 h -1 bar -1 、50L m -2 h -1 bar -1 、100L m -2 h -1 bar -1 、150L m -2 h -1bar -1 、200L m -2 h -1 bar -1 、250L m -2 h - 1 bar -1 、300L m -2 h -1 bar -1 or any value in between.

[0012] In some embodiments, the water flux of the reverse osmosis membrane is 30-250 L m -2 h -1 bar -1 .

[0013] In some embodiments, the water flux of the reverse osmosis membrane is 30-200 L m -2 h -1 bar -1 .

[0014] In some embodiments, the ion rejection rate of the reverse osmosis membrane is 75-97%, for example, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94% or any value therebetween.

[0015] In some embodiments, the reverse osmosis membrane has an ion rejection rate of 80-95%.

[0016] In some embodiments, the reverse osmosis membrane has a thickness of 550 nm-25 μm, for example, 1000 nm, 1300 nm, 1600 nm, 1900 nm, 2200 nm, 2500 nm or any value therebetween.

[0017] In some embodiments, the reverse osmosis membrane has a thickness of 580 nm-25 μm.

[0018] In some embodiments, the reverse osmosis membrane has a thickness of 1 μm-20 μm.

[0019] The present invention prepares a self-supporting reverse osmosis membrane by combining metal oxide nanobelts prepared from clay minerals with flexible graphene oxide through coordination self-assembly and combining them with a polymer matrix, which not only improves filtration efficiency, selectivity and mechanical properties, but also expands the application field of clay minerals.

[0020] In some embodiments, the metal oxide nanobelt material has a ribbon length of 500-1800 nm, for example, 600 nm, 800 nm, 1000 nm, 1200 nm, 1400 nm, 1600 nm, 1800 nm or any value therebetween.

[0021] In some embodiments, the bandwidth of the metal oxide nanobelt material is 17 to 50 nm, for example, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm or any value therebetween.

[0022] In some embodiments, the thickness of the metal oxide nanobelt material is 6.2 to 15.7 nm; for example, 6.5 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm or any value therebetween.

[0023] In some embodiments, the length of the graphene oxide nanosheet material is 10 to 22 μm, for example, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm or any value therebetween.

[0024] In some embodiments, the width of the graphene oxide nanosheet material is 0.5-8 μm, for example, 0.6 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or any value therebetween.

[0025] In some embodiments, the graphene oxide nanosheet material has a thickness of 0.7 to 2.1 nm, for example, 0.8 nm, 1 nm, 1.2 nm, 1.4 nm, 1.6 nm, 1.8 nm, 2 nm or any value therebetween.

[0026] In some embodiments, the metal oxide nanobelts are nanobelts prepared from clay minerals.

[0027] In some embodiments, the metal oxide nanobelts are prepared from palygorskite.

[0028] In some embodiments, the method for preparing the metal oxide nanobelts includes: etching a clay mineral using an alkaline solution.

[0029] In some embodiments, the alkaline solution is one or more of an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution.

[0030] In some embodiments, the clay mineral includes palygorskite. The raw material of the present invention uses natural palygorskite, which is cheap and easy to obtain. The abundant natural clay minerals are of great value in preparing rigid metal oxide nanobelts. Palygorskite (PAL) is composed of magnesium oxide octahedron (MgO) and silicon oxide tetrahedron (SiO2). SiO2 amphoteric oxide can be etched with alkaline solution to obtain rigid metal oxide nanobelts.

[0031] In some embodiments, the mass ratio of the clay mineral to the alkaline solution is 0.1-0.5:100; for example, 0.1:100, 0.15:100, 0.2:100, 0.25:100, 0.3:100, 0.35:100, 0.4:100, 0.45:100, 0.5:100 or any value therebetween.

[0032] In some embodiments, the etching temperature is 120-180° C., for example, 120° C., 130° C., 140° C., 150° C., 160° C., 170° C., 180° C., or any value therebetween.

[0033] In some embodiments, the etching time is 24-48 hours, for example, 30 hours, 35 hours, 40 hours, 45 hours or any value therebetween.

[0034] In some embodiments, the preparation method of the metal oxide nanobelt material comprises: preparing 100 mL of saturated NaOH solution, dispersing 0.1-0.5 g of palygorskite nanorods in the saturated NaOH solution, stirring evenly, loading into a high-pressure reactor, and reacting at 120-180° C. for 24-48 hours. After the reaction is completed, centrifuge and wash three times, and then disperse it in 100 mL of deionized water for ultrasonic treatment for 10-15 hours. After ultrasonic treatment, let it stand for 5-10 minutes, take 50 mL of the upper suspension and collect it by centrifugation at 8000-12000 rpm, wash it 3 times with deionization, and freeze-dry it to obtain the metal oxide nanobelt material.

[0035] In some embodiments, the method for preparing the graphene oxide nanosheet material comprises: mixing a mixture comprising graphite, concentrated sulfuric acid, and NaNO 3 with an oxidant, and sequentially performing a first reaction and a second reaction.

[0036] In some embodiments, the method for preparing the graphene oxide nanosheet material comprises: removing MnO4 with ultrapure water and hydrogen peroxide after the second reaction. - Then, hydrochloric acid is used to remove metal ions.

[0037] In some embodiments, the mixture comprising graphite, concentrated sulfuric acid, and NaNO3 is stirred in an ice bath for 10-60 min. In some embodiments, the mass ratio of graphite to NaNO3 is 5:1-1:5; for example, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5 or any value therebetween.

[0038] In some embodiments, the mass concentration of the concentrated sulfuric acid is 90-98%, for example, 90%, 92%, 94%, 96%, 98% or any value therebetween.

[0039] In some embodiments, the mass ratio of the graphite to the oxidant is 1:3-1:6; for example, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6 or any value therebetween.

[0040] In some embodiments, the temperature at which the mixture comprising graphite, concentrated sulfuric acid, and NaNO3 is mixed with the oxidant is less than 15°C.

[0041] In some embodiments, the temperature of the first reaction is 20-50°C, such as 22°C, 28°C, 34°C, 40°C, 46°C, 50°C or any value therebetween.

[0042] In some embodiments, the temperature of the second reaction is 80-120°C, for example, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C or any value therebetween.

[0043] In some embodiments, the preparation method of the graphene oxide nanosheet material includes: mixing graphite with NaNO3 and 98% H2SO4, and stirring in an ice bath for 15-50 minutes; then, slowly adding KMnO4 within 80-100 minutes to keep the mixture temperature below 15°C; transferring the reaction system to a 15-40°C water bath for 15-50 minutes, and then slowly adding distilled water; continuing the reaction in an 80-120°C oil bath for 24 hours; then adding ultrapure water and 20-40% H2O2 in sequence to remove residual MnO4 - and rinsed with 5-15% HCl to remove residual metal ions; the obtained solid phase was repeatedly rinsed with ultrapure water until the pH value was neutral; finally, the ultrasonically treated graphene oxide aqueous dispersion was centrifuged at 5000-7000 rpm for 20-30 minutes, and the supernatant of the graphene oxide sheets dispersed in the water was collected and freeze-dried to obtain graphene oxide nanosheet material.

[0044] In a second aspect, the present invention provides a method for preparing a reverse osmosis membrane, comprising: mixing a reaction solution comprising the composition described in the first aspect of the present invention with a polymer matrix.

[0045] In some embodiments, the preparation method comprises: (1) dispersing the composition described in the first aspect of the present invention in a solvent, ultrasonicating, stirring and reacting to obtain a reaction liquid; (2) dispersing a polymer in a solvent to obtain a polymer matrix; (3) mixing and stirring the reaction liquid and the polymer matrix to obtain a coating slurry; (4) coating with the coating slurry, drying, and then immersing in water to remove the reverse osmosis membrane from the polymer matrix to obtain the reverse osmosis membrane.

[0046] In some embodiments, in step (1), the stirring reaction time is 12-24 hours, for example, 12 hours, 15 hours, 18 hours, 21 hours, or 24 hours.

[0047] In some embodiments, in step (1), the ultrasound time is 15-50 min, for example, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min.

[0048] In some embodiments, in step (2), the polymer is selected from one or more of polyacrylonitrile, polyimide or polysulfone.

[0049] In some embodiments, the solvent in step (1) and step (2) is selected from one or more of DMF, DMSO and dichloromethane.

[0050] In some embodiments, in step (3), the content of the polymer in the coating slurry is 5-15wt%, for example, 5wt%, 7wt%, 9wt%, 11wt%, 13wt%, 15wt%.

[0051] In some embodiments, in step (3), the content of the polymer in the coating slurry is 10 wt %.

[0052] In some embodiments, in step (3), the mixing and stirring time is 12-24 hours, for example, 12 hours, 15 hours, 18 hours, 21 hours, or 24 hours.

[0053] In some embodiments, in step (3), the coating method is Meeller rod coating.

[0054] In some embodiments, the preparation method comprises:

[0055] (1) dispersing the composition according to the first aspect of the present invention in DMF, ultrasonicating for 15-50 min, stirring and reacting for 12-24 h to obtain a reaction solution;

[0056] (2) dispersing the polymer in DMF to obtain a polymer matrix;

[0057] (3) mixing and stirring the reaction solution and the polymer matrix for 12-24 hours to obtain a coating slurry;

[0058] (4) coating with the coating slurry, drying, and then immersing in water for 1 to 2 minutes to remove the reverse osmosis membrane from the polymer matrix to obtain the reverse osmosis membrane.

[0059] In a third aspect, the present invention provides a use of the reverse osmosis membrane described in the first aspect of the present invention in desalination of rare earth high-salt wastewater and / or seawater desalination.

[0060] In a fourth aspect, the present invention provides a seawater desalination method, using the reverse osmosis membrane described in the first aspect of the present invention to intercept NaCl molecules in the seawater.

[0061] The present invention uses metal oxide nanobelts as one of the assembly units, and performs biomimetic mixed dimensional assembly with graphene oxide flakes through coordination bonds, that is, the principle of forming strong coordination bonds by the functional groups carboxyl and hydroxyl of metal oxide nanobelts and graphene oxide, and then combines the polymer matrix, adopts the Mehler rod coating technology, and prepares a large-area self-supporting mixed dimensional assembled reverse osmosis membrane, which has excellent water flux, high ion interception rate and high mechanical stability, solves the problem that the structure and physicochemical stability of pure graphene oxide film are low, and it is easy to swell when it encounters water, and solves the challenge that the film is difficult to be self-supported for a long time. Not only can the filtration efficiency, selectivity and mechanical properties be improved, but also the application field of clay minerals is expanded. Further, the present invention adopts the biomimetic mixed dimensional assembly principle, and the preparation operation is simple, green and environmentally friendly, and can achieve low cost and high efficiency removal of NaCl. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 a is a layered film assembled from graphene oxide nanosheets;

[0063] Figure 1 b is a schematic diagram of a graphene oxide reverse osmosis membrane based on mixed dimensional assembly prepared according to a specific embodiment of the present invention;

[0064] Figure 2 a is a graphene oxide-based polymer slurry prepared according to one embodiment of the present invention;

[0065] Figure 2 b is a graphene oxide reverse osmosis membrane based on mixed dimensional assembly prepared according to one embodiment of the present invention;

[0066] Figure 3 is a scanning electron microscope image of a graphene oxide reverse osmosis membrane based on mixed dimensional assembly prepared in Example 1 of the present invention;

[0067] Figure 4 It is a performance diagram of high-salt wastewater desalination and seawater desalination of the graphene oxide reverse osmosis membrane based on mixed dimensional assembly prepared in Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0068] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention.

[0069] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0070] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0071] Except for the interception rate, "%" in the present invention refers to mass percentage.

[0072] The water flux in the present invention refers to the amount of water passing through the membrane area per unit time.

[0073] The rejection rate in the present invention refers to the retention capacity of the membrane for NaCl solute molecules.

[0074] In each embodiment of the present invention, the ribbon length of the metal oxide nanobelt material is 500-1800 nm; the bandwidth of the metal oxide nanobelt material is 17-50 nm; the thickness of the metal oxide nanobelt material is 6.2-15.7 nm; the length of the graphene oxide nanosheet material is 10-22 μm; the width of the graphene oxide nanosheet material is 0.5-8 μm; the thickness of the graphene oxide nanosheet material is 0.7-2.1 nm.

[0075] Example 1

[0076] (1) Preparation of graphene oxide nanosheets (GO NS): Graphite powder (2.0 g) and NaNO3 (1.0 g) were mixed with 50 mL of 98% H2SO4 and stirred in an ice bath for 30 min. Then, KMnO4 (6 g) was slowly added over 90 min to keep the mixture temperature below 15°C. Subsequently, the reaction system was transferred to a 35°C water bath for 30 min, and 100 mL of distilled water was slowly added. After that, the reaction was continued in a 98°C oil bath for 24 h. Then, 100 mL of ultrapure water and 10 mL of 30% H2O2 were added in sequence to remove residual MnO4. -. The resulting bright yellow mixture was filtered and rinsed with 10% HCl to remove residual metal ions. The resulting solid phase was repeatedly rinsed with ultrapure water until the pH value was neutral. Finally, the ultrasonically treated GO aqueous dispersion was centrifuged at 6000 rpm for 15 minutes. The supernatant of the GO sheets dispersed in water was collected and freeze-dried to obtain graphene oxide nanosheet material.

[0077] (2) Preparation of metal oxide nanobelts (MO NR): First, prepare 100 mL of saturated NaOH solution, disperse 0.5 g of palygorskite nanorods (PAL NR) in the saturated NaOH solution, stir evenly, put into a high-pressure reactor, and react at 160°C for 48 hours. After the reaction is completed, centrifuge and wash three times, then disperse it in 100 mL of deionized water and ultrasonically treat it for 12 hours. After ultrasonic treatment, let it stand for 5 minutes, take 50 mL of the upper suspension and collect it by centrifugation at 10,000 rpm, wash it three times with deionized water, and freeze-dry it to obtain metal oxide nanobelt (MONR) material.

[0078] (3) Preparation of reverse osmosis membrane: First, metal oxide nanobelts (MO NR, 65 mg) and single-layer graphene oxide nanosheets (GO NS, 65 mg) were taken at a mass ratio of 1:1, respectively, and dispersed in 4.5 g N,N-dimethylformamide (DMF), ultrasonicated for 30 min to make them dispersed evenly, and stirred vigorously at room temperature for 12 h to obtain a coordination reaction solution. Subsequently, 1 g of polyacrylonitrile (PAN) was dispersed in 4.5 g of DMF to obtain a polymer matrix of PAN. Finally, the coordination reaction solution and the polymer matrix were mixed and stirred for 12 h to make the mass fraction of PAN 10 wt%, and about 10 mL of coating slurry was obtained. Subsequently, the mixed-dimensional assembled graphene oxide reverse osmosis membrane was prepared by the Myler rod coating assembly method. After the reverse osmosis membrane was dried, the reverse osmosis membrane and the polymer substrate were transferred into water, and the reverse osmosis membrane and the polymer substrate were completely immersed in water for 2 minutes. Then the reverse osmosis membrane gradually fell off the polymer substrate to obtain a wet graphene oxide reverse osmosis membrane, which was dried at room temperature for the next step of testing and characterization, as shown in Table 1.

[0079] Example 2

[0080] (1) Preparation of graphene oxide nanosheets (GO NS): Graphite powder (4.0 g) and NaNO3 (2.0 g) were mixed with 100 mL of 98% H2SO4 and stirred in an ice bath for 60 min. Then, KMnO4 (12 g) was slowly added over 90 min to keep the mixture temperature below 15°C. Subsequently, the reaction system was transferred to a 35°C water bath for 30 min, and 200 mL of distilled water was slowly added. After that, the reaction was continued in a 98°C oil bath for 24 h. Then, 200 mL of ultrapure water and 20 mL of 30% H2O2 were added in sequence to remove residual MnO4. - . The resulting bright yellow mixture was filtered and rinsed with 10% HCl to remove residual metal ions. The resulting solid phase was repeatedly rinsed with ultrapure water until the pH value was neutral. Finally, the ultrasonically treated GO aqueous dispersion was centrifuged at 6000 rpm for 15 minutes. The supernatant of the GO sheets dispersed in water was collected and freeze-dried to obtain graphene oxide nanosheet material.

[0081] (2) Preparation of metal oxide nanobelts (MO NR): First, prepare 100 mL of saturated NaOH solution, disperse 0.4 g of palygorskite nanorods (PAL NR) in the saturated NaOH solution, stir evenly, put into a high-pressure reactor, and react at 160°C for 48 hours. After the reaction is completed, centrifuge and wash three times, then disperse it in 100 mL of deionized water and ultrasonically treat it for 12 hours. After ultrasonic treatment, let it stand for 5 minutes, take 50 mL of the upper suspension and collect it by centrifugation at 10,000 rpm, wash it three times with deionization, and freeze-dry it to obtain metal oxide nanobelt (MONR) material.

[0082] (3) Preparation of reverse osmosis membrane: First, metal oxide nanobelts (MO NR, 65 mg) and single-layer graphene oxide nanosheets (GO NS, 130 mg) were taken at a mass ratio of 1:2, respectively, and dispersed in 4.5 g N,N-dimethylformamide (DMF), ultrasonicated for 30 min to make them evenly dispersed, and stirred vigorously at room temperature for 12 h to obtain a coordination reaction solution. Subsequently, 1 g of polyacrylonitrile (PAN) was dispersed in 4.5 g of DMF to obtain a polymer matrix of PAN. Finally, the coordination reaction solution and the polymer matrix were mixed and stirred for 12 h to make the mass fraction of PAN 10 wt%, and about 10 mL of coating slurry was obtained. Subsequently, the Mehler rod coating assembly method was used to prepare a graphene oxide reverse osmosis membrane based on mixed dimensional assembly. After the reverse osmosis membrane was dried, the reverse osmosis membrane together with the polymer substrate was transferred into water, and the reverse osmosis membrane and the polymer substrate were completely immersed in water for 1 minute. Then the reverse osmosis membrane gradually fell off the polymer substrate to obtain a wet graphene oxide reverse osmosis membrane, which was dried at room temperature for the next step of testing and characterization.

[0083] Example 3

[0084] (1) Preparation of graphene oxide nanosheets (GO NS): Graphite powder (6.0 g) and NaNO3 (3.0 g) were mixed with 150 mL of 98% H2SO4 and stirred in an ice bath for 60 min. Then, KMnO4 (18 g) was slowly added over 90 min to keep the mixture temperature below 15°C. Subsequently, the reaction system was transferred to a 35°C water bath for 30 min, and 300 mL of distilled water was slowly added. After that, the reaction was continued in a 98°C oil bath for 24 h. Then, 300 mL of ultrapure water and 30 mL of 30% H2O2 were added in sequence to remove residual MnO4. - . The resulting bright yellow mixture was filtered and rinsed with 10% HCl to remove residual metal ions. The resulting solid phase was repeatedly rinsed with ultrapure water until the pH value was neutral. Finally, the ultrasonically treated GO aqueous dispersion was centrifuged at 6000 rpm for 15 minutes. The supernatant of the GO sheets dispersed in water was collected and freeze-dried to obtain graphene oxide nanosheet material.

[0085] (2) Preparation of metal oxide nanobelts (MO NR): First, prepare 100 mL of saturated NaOH solution, disperse 0.2 g of palygorskite nanorods (PAL NR) in the saturated NaOH solution, stir evenly, put into a high-pressure reactor, and react at 160°C for 48 hours. After the reaction is completed, centrifuge and wash three times, then disperse it in 100 mL of deionized water and ultrasonically treat it for 12 hours. After ultrasonic treatment, let it stand for 5 minutes, take 50 mL of the upper suspension and collect it by centrifugation at 10,000 rpm, wash it three times with deionized water, and freeze-dry it to obtain metal oxide nanobelt (MONR) material.

[0086] (3) Preparation of reverse osmosis membrane: First, metal oxide nanobelts (MO NR, 65 mg) and single-layer graphene oxide nanosheets (GO NS, 195 mg) were taken at a mass ratio of 1:3, respectively, and dispersed in 4.5 g N,N-dimethylformamide (DMF), ultrasonicated for 30 min to make them dispersed evenly, and stirred vigorously at room temperature for 24 h to obtain a coordination reaction solution. Subsequently, 1 g of polyacrylonitrile (PAN) was dispersed in 4.5 g of DMF to obtain a polymer matrix of PAN. Finally, the coordination reaction solution and the polymer matrix were mixed and stirred for 24 h to make the mass fraction of PAN 10 wt%, and about 10 mL of coating slurry was obtained. Subsequently, the Mehler rod coating assembly method was used to prepare a graphene oxide reverse osmosis membrane based on mixed dimensional assembly. After the reverse osmosis membrane was dried, the reverse osmosis membrane together with the polymer substrate was transferred into water, and the reverse osmosis membrane and the polymer substrate were completely immersed in water for 2 minutes. Then the reverse osmosis membrane gradually fell off the polymer substrate to obtain a wet graphene oxide reverse osmosis membrane, which was dried at room temperature for the next step of testing and characterization.

[0087] Table 1

[0088] Reverse osmosis membrane thickness (μm) <![CDATA[Water flux (L -1 m -2 h -1 bar -1 )]]> Retention rate (%) Example 1 1.2 187.4 83.3 Example 2 12.7 42.5 84.2 Example 3 15.0 33.9 92.7

[0089] Figure 1 a is a layered membrane assembled from graphene oxide nanosheets. Water molecules will greatly weaken the interaction between graphene oxide layers, so it will swell when it comes into contact with water to produce non-selective channels. Figure 1 b is a graphene oxide reverse osmosis membrane based on mixed dimensional assembly. Due to the strong coordination interaction between graphene oxide and metal oxide nanobelts, the bionic mixed dimensional assembled reverse osmosis membrane will not form non-selective channels in an aqueous environment and has the potential for high-salt wastewater desalination and seawater desalination.

[0090] Figure 2 The graphene oxide-based polymer slurry prepared by the present invention ( Figure 2 a) and large-area reverse osmosis membranes prepared by Myler rod coating ( Figure 2 b) The graphene oxide nanosheets and metal oxide nanobelts uniformly dispersed in DMF are mixed and self-assembled by coordination and polymer combination to form a viscous slurry, such as Figure 2 As shown in a, a self-supporting large-area reverse osmosis membrane was subsequently prepared by the Myler rod coating technique, as shown in Figure 2 As shown in b.

[0091] Figure 3 This is a scanning electron microscope image of the graphene oxide reverse osmosis membrane based on mixed dimensional assembly prepared in Example 1. Figure 3 The bionic reverse osmosis membrane has a flat and complete surface without pinhole defects. The figure also shows the cross section of the reverse osmosis membrane, showing that the thickness of the reverse osmosis membrane is about 1200nm.

[0092] The performance of the reverse osmosis membrane assembled by the biomimetic mixed dimension assembly of the present invention in retaining sodium chloride (NaCl, sodium salt) was tested by dead-end filtration and cross-flow flat membrane device, as shown in Table 1 and Figure 4 As shown in the figure, the biomimetic hybrid dimensional assembled reverse osmosis membrane has a high retention effect on NaCl molecules, showing that the reverse osmosis membrane has great potential in the field of high-salinity wastewater desalination and / or seawater desalination. Specifically, the biomimetic reverse osmosis membrane has a high retention selectivity of up to 92.7% for NaCl solute molecules and has a 33.9L -1 m -2 h -1 bar -1 of water flux (Example 3).

[0093] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A reverse osmosis membrane based on mixed dimensional assembly, mainly obtained by coordination self-assembly of graphene oxide nanosheet materials and metal oxide nanobelt materials; The mass ratio of the metal oxide nanobelt material to the graphene oxide nanomaterial is 1:(0.2-6).

2. The reverse osmosis membrane according to claim 1, characterized in that The mass ratio of the metal oxide nanobelt material to the graphene oxide nanomaterial is 1:(2.5-5).

3. The reverse osmosis membrane according to claim 1, characterized in that The water flux of the reverse osmosis membrane is 20-300L m -2 h -1 bar -1 , and / or The ion rejection rate of the reverse osmosis membrane is 75-97%, and / or The thickness of the reverse osmosis membrane is 550 nm to 25 μm.

4. The reverse osmosis membrane according to claim 1, characterized in that The water flux of the reverse osmosis membrane is 30-250 Lm -2 h -1 bar -1 .

5. The reverse osmosis membrane according to claim 1, characterized in that The ion rejection rate of the reverse osmosis membrane is 80-95%.

6. The reverse osmosis membrane according to claim 1, characterized in that The thickness of the reverse osmosis membrane is 580nm-25μm.

7. The reverse osmosis membrane according to claim 1, characterized in that The thickness of the reverse osmosis membrane is 1 μm-20 μm.

8. The reverse osmosis membrane according to claim 1, characterized in that The metal oxide nanobelt material has a ribbon length of 500 to 1800 nm; and / or The bandwidth of the metal oxide nanobelt material is 17-50 nm; and / or The thickness of the metal oxide nanobelt material is 6.2-15.7 nm; and / or The length of the graphene oxide nanosheet material is 10-22 μm; and / or The width of the graphene oxide nanosheet material is 0.5-8 μm; and / or The thickness of the graphene oxide nanosheet material is 0.7-2.1 nm.

9. The reverse osmosis membrane according to any one of claims 1 to 8, characterized in that The metal oxide nanobelt is prepared from clay minerals.

10. The reverse osmosis membrane according to any one of claims 1 to 8, characterized in that The metal oxide nanobelt is prepared by palygorskite.

11. The reverse osmosis membrane according to any one of claims 1 to 8, characterized in that The method for preparing the metal oxide nanobelt comprises: etching clay minerals with an alkaline solution.

12. The reverse osmosis membrane according to claim 11, characterized in that The alkaline solution is one or more of a sodium hydroxide aqueous solution or a potassium hydroxide aqueous solution; The clay mineral comprises palygorskite; and / or The mass ratio of the clay mineral to the alkaline solution is 0.1-0.5:100; and / or, The etching temperature is 120-180° C.; and / or, The etching time is 24-48h.

13. The reverse osmosis membrane according to any one of claims 1 to 8, characterized in that The method for preparing the graphene oxide nanosheet material comprises: mixing a mixture including graphite, concentrated sulfuric acid and NaNO3 with an oxidant, and sequentially performing a first reaction and a second reaction.

14. The reverse osmosis membrane according to claim 13, characterized in that The mass ratio of graphite to NaNO3 is 5:1-1:5; and / or The mass concentration of the concentrated sulfuric acid is 90-98%; and / or The mass ratio of graphite to oxidant is 1:3-1:6; and / or The oxidant is KMNO4, and / or The mixing temperature is below 15°C; and / or The temperature of the first reaction is 20-50°C; and / or The temperature of the second reaction is 80-120°C. 15 . A method for preparing a reverse osmosis membrane according to claim 1 , comprising the following steps: mixing a reaction solution containing graphene oxide nanosheet material and metal oxide nanobelt material with a polymer matrix.

16. The preparation method according to claim 15, characterized in that: The mass ratio of the metal oxide nanobelt material to the graphene oxide nanomaterial is 1:(0.2-6).

17. The preparation method according to claim 15, characterized in that: The mass ratio of the metal oxide nanobelt material to the graphene oxide nanomaterial is 1:(2.5-5).

18. The preparation method according to claim 15, characterized in that: The preparation method comprises: (1) dispersing the metal oxide nanobelt material and the graphene oxide nanosheet material in a solvent, ultrasonicating, stirring and reacting to obtain a reaction solution; (2) dispersing the polymer in a solvent to obtain a polymer matrix; (3) mixing and stirring the reaction solution and the polymer matrix to obtain a coating slurry; (4) The reverse osmosis membrane is removed from the polymer matrix by coating with the coating slurry, drying, and then immersing in water to obtain the reverse osmosis membrane.

19. The preparation method according to claim 18, characterized in that: In step (1), the stirring reaction time is 12-24 hours; and / or, In step (1), the ultrasonic treatment time is 15-50 min; and / or In step (2), the polymer is selected from one or more of polyacrylonitrile, polyimide or polysulfone, and / or The solvent in step (1) and step (2) is selected from one or more of DMF, DMSO and dichloromethane; and / or In step (3), the content of the polymer in the coating slurry is 5-15wt%; and / or In step (3), the mixing and stirring time is 12-24 hours; and / or In step (3), the coating method is the Myler rod coating method.

20. Use of the reverse osmosis membrane according to any one of claims 1 to 14 in rare earth high-salinity wastewater treatment and / or seawater desalination.

21. A seawater desalination method, comprising intercepting NaCl molecules in the seawater by using the reverse osmosis membrane according to any one of claims 1 to 14.